Accuracy of fecal calprotectin and endoscopic narrow band imaging in the prediction of severity of inflammatory bowel diseases - Shahma, Abu; Anees, Afzal; Yaqoob Hassan; Hasan, Nadimul; Daiyyan, Mohammad (International Journal of Research in Medical Sciences, 2023)
Background: Fecal calprotectin is a noninvasive and accurate marker of inflammatory bowel disease. In addition to aiding in diagnosis, it also predicts inflammatory bowel disease (IBD) relapses and the severity of the disease. Objectives of current study were evaluate the accuracy of Fecal calprotectin and Narrow band imaging for prediction severity in inflammatory bowel disease. Methods: After informed written consent and ethical clearance, the study prospectively included 50 patients of IBD. Quantitative measurement of Calprotectin was done by ELISA kit (Eagle Biosciences, Nashua). Endoscopy activity was calculated using Narrow band imaging. Results: Out of 50 patients, Males outnumbered the females with a ratio of 2.1. Increased frequency of stools was the most common symptom (94%). 39 (78%) patients had features ulcerative colitis while as 9 (18%) patients had features of Crohn’s disease. Total of 42 (84%) patients had elevated levels of Fecal Calprotectin. The severity of IBDs increased significantly when the Fecal Calprotectin level rises (p value >0.05). The relationship between endoscopic and histological scores to detect disease severity in IBD was statistically insignificant (p value=0.85). The accuracy of the fecal calprotectin levels was found to be 84%, sensitivity 87.5%, and specificity was 50%. The positive and negative predictive values were 97.6% and 12.55% respectively. 47 (94%) patients received medical treatment. 3 (7.7%) patients of UC were subjected to surgical intervention. Conclusions: Fecal calprotectin is a valuable and non-invasive marker with good sensitivity and specificity for the diagnosis, evaluation of the severity, and monitoring of IBD activity.